Time Parameters of the Blink Reflex in Normal Subjects - Brooks, J.B.B.; Jardim, M.R.; Papais-Alvarenga, R.M.; Fragoso, Y.D. (Нейрофизиология, 2014)
Our study was aimed at estimating normal time values for the EMG waves recorded in
the blink reflex test. The group examined included 400 healthy subjects (226 women and
174 men, with mean age about 50 years). There was no significant difference between the
ages of the male and female subjects. The mean latency of the R1 wave in the response was
10.3 msec, while R2 was obtained after 32.5 msec, on average. The contralateral response
component R2c was observed after 34.4 msec, on average. Gender did not influence the results,
while age had a significant effect on R1 (P = 0.029) and R2c (P = 0.0003). The older the subject,
the longer the latencies of the above waves. The data obtained on a rather large sampling of
the tested subjects can be useful as normography for medical and neurophysiological purposes. У своєму дослідженні ми оцінювали нормальні часові параметри хвиль ЕМГ, що реєструвалися при тестуванні рефлексу кліпання. До обстеженої групи ввійшли 400 здорових осіб
(226 жінок та 174 чоловіки, середній вік близько 50 років)
без істотної різниці віку в групах чоловіків і жінок. Середній латентний період (ЛП) хвилі R1 у складі досліджуваної
рефлекторної відповіді складав 10.30, а хвилі R2 – 32.51 мс.
Контралатеральний компонент відповіді R2c виникав із середнім ЛП 34.43 мс. Стать обстежених не впливала істотно
на ці значення; в той же час останні демонстрували значну залежність від віку (R1, P = 0.029; R2c, P = 0.0003; чим
старші були обстежені, тим довші були вказані ЛП). Результати, отримані на досить великій дослідженій групі здорових осіб, можуть бути корисними як нормографічні дані для
медичних та нейрофизіологічних цілей.